(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article presents a linguocognitive analysis of conceptual metaphors in Uzbek and English within the framework of the anthropocentric paradigm. The primary objective of the study is to identify how human cognition and cultural values are expressed through metaphorical constructions. Comparative analysis demonstrates that, while universal cognitive tendencies exist in both languages, cultural context and language-specific features play a decisive role in shaping conceptual metaphors. The findings provide valuable insights for linguocultural studies and cognitive linguistics research.